RANCANG BANGUN ALAT UJI TARIK SERAT BERBASIS DIGITAL - mukhlis muslimin mallomoang (Machine : Jurnal Teknik Mesin, 2022)
The purpose of this research is to design and manufacture tensile test equipment that can determine the tensile load of natural fibers which is a parameter to determine the mechanical property of the material. The research method is to make designs through Autodesk Fusion 360 software, manufacture and supply components, assembling and test fiber tensile test equipment. In single fiber testing, the test specimen is made according to the ASTM ASTM 3379-02 standard. The results of this research are one unit of digital fiber tensile test equipment with a maximum load capacity of 100 N (10 kgf), a gripping capacity of 600 mm x 30 mm. While testing this fiber tensile test equipment on coconut single fiber material, the tensile strength (F) is between 16.42 N to 29.31 N. And from the calculation of tensile strength (σ) the tensile strength of coconut fiber is 61.70 N/mm2 to 83.80 N/mm2. From the results of this study, it was concluded that the tensile test equipment made can operate as expected to determine the tensile load (F) as well as single so that through the test results this tool can be determined the tensile strength of single fiber material.